(untitled) (Asian Journal of Medical and Biological Research, 2022)
Fish hatcheries are generally regarded as the first step in the process of aquaculture development in any given nation. Fish breeding plays an important part in the process of supplying fry and fingerling to the farmers. The current study was conducted to identify the effectiveness of using dry and wet carp pituitary gland (CPG) in the induced breeding of mirror carp (Cyprinus carpio var. specularis), at Banchte Sheka fish hatchery Arabpur, Jashore from November to December 2021. The 1st dose of hormone, both for male and female brood fishes were injected with dry & wet PG at 0.8 mg PG/kg body weight. After 6 hours of the 1st dose, only female brood fishes were injected with the 2nd dose of hormone at 3 mg PG/kg body weight. After 6-7 hours of injection of 2nd dose, brood fishes became ready to spawn. The fertilized eggs were hatched after 42-48 hours. The ovulation rates were 100%. The fertilization rates were 88.3 % and 91.2% for wet and dry PG, respectively. The hatching rates were 84.2% and 87.5%, respectively. The survival rates were 79.5% and 83.3%, respectively. Therefore, dry CPG is highly recommended to hatchery owners considering the rate of fertilization, survival rate and availability. The information that has been offered here will be helpful to the owners of hatcheries when it comes to choosing the sort of pituitary gland to use in the breeding operation. Asian J. Med. Biol. Res. 2022, 8 (2), 115-122